Comparison between Effects of Midazolam and Dexmedetomidine as Sedative in Elective Caesarean Section under Spinal Anaesthesia - Karim, Md Enayet; Rashid, RAM Mustafijur; Akram, Mohammad Saleh; Ershad, Reza (Community Based Medical Journal, 2023)
This randomized clinical trial compares midazolam and dexmedetomidine in terms of onset and recovery of sedation, haemodynamic effects, respiratory effects, and adverse effects of both the drugs in elective Caesarian section under spinal anaesthesia. The study included 60 ASA grade-I patients between age 20- and 40-years undergoing elective Caesarean sections under subarachnoid anaesthesia, from January 2022 to June 2022. Patients were randomly allocated to one of the two groups: midazolam group (Group-I, n=30), who received midazolam in a single dose of 0.10mg/kg and Dexmedetomidine group (Group-II, n=30), who received dexmedetomidine in a single dose of 2mcg/kg. Spinal anaesthesia was conducted by injecting a hyperbaric solution of 0.5% bupivacaine 3ml through a 25G spinal needle at L3-4 level. All parameters were documented at 5-minute intervals until arousal of the patient. The onset of sedation i.e., time from IV (intravenous) injection of Midazolam or Dexmedetomidine to closure of eye lids (OAA/S score of 3) and the arousal time from sedation i.e., time from closing of the eye lids to OAA/S score of 5 (patient is awake clinically) were noted. Any complication during operation was documented. The patient’s satisfaction with the sedation was assessed by the 5-point ‘Likert verbal rating scale’. There was no significant difference of mean blood pressure and mean heart rate between the two groups at different time intervals (P>0.05). Time of onset of sedation was significantly delayed in dexmedetomidine group (P<0.05). Duration of sedation was comparable between the two groups (P>0.05). Incidence of peroperative complications were comparable between the two groups (P>0.05). Haemodynamic effects and adverse effects of two drugs were comparable. Therefore, it is recommended that either midazolam or dexmedetomidine can be used for sedation in single dose technique during subarachnoid block for Caesarean section. CBMJ 2023 January: Vol. 12 No. 01 P: 99-106